2016
DOI: 10.17344/acsi.2015.2068
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Design Approach for Methylene Blue Dye Removal in Aqueous Environment by Nitrilotriacetic Modified Banana Pith

Abstract: Native banana pith (NBP) was modified by using nitrilotriacetic acid to increase its efficiency and adsorption capacity for methylene blue (MB) dye. The effect of various parameters such as pH, contact time, initial dye concentrations and adsorbent dosage were studied. Equilibrium data could be fitted into Langmuir isotherm and the maximum adsorption capacity of the NBP and NTA-BP is 100 and 142.86 mg/g, respectively. The IR spectrum of NBP and NTA-BP showed the presence of both carboxyl and hydroxyl groups. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…MB dye removal has positive and direct correlation with solution pH as well as adsorbent mass (Figure b). The probable explanation is higher accessible binding sites at more and alkaline pH and accelerate MB binding to Sn 6 O 4 (OH) 4 ‐NPs‐AC surface . The problem of high adsorbent amount may cause interference between binding sites or insufficiently of dye ions in the solution with respect to available binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…MB dye removal has positive and direct correlation with solution pH as well as adsorbent mass (Figure b). The probable explanation is higher accessible binding sites at more and alkaline pH and accelerate MB binding to Sn 6 O 4 (OH) 4 ‐NPs‐AC surface . The problem of high adsorbent amount may cause interference between binding sites or insufficiently of dye ions in the solution with respect to available binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, conducting 32 experiments permits the researchers for full study of all regions. Each experimental run was analyzed and the response was correlated with five input factors by using the following quadratic polynomial equation 29 :…”
Section: Central Composite Design (Ccd)mentioning
confidence: 99%
“…The encounter difficulties are serious peaks overlapping that subsequently impossible their direct determination in mixture using general equation like Beer-Lambert 26-28. Conventional and classical optimization protocol (one at a time) failed to give useful knowledge about the interaction between variables while requiring intensive labor and consuming long time because of requiring high number of experiments. Central composite design (CCD) under response surface methodology (RSM) can efficiently be applied for handling both variables involved and responses without suffering above-mentioned draw backs [29][30][31] .This approach enables researchers to make a suitable predicative model to apply for several factors even in the presence of complex interactions to describe responses and find the optimal conditions with less time elapsed [32][33][34][35] . In this work, MWCNT was modified with Schiff base-like structure following its reaction with N-(3-nitro-benzylidene)-N0-trimethoxysilylpropyl-ethane-1, 2-diamine (NBATSPED-MWCNT).A novel adsorbent followed by the characterization using different techniques such as Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 99%
“…The usage of these dyes has continuously increased and it has been reported that there are more than 100,000 commercial dyes with a rough estimated production of 7 × 10 5 to 1 × 10 6 tons per year. 1,2 Although this colored pollutant imparts only a small fraction of the total organic load in wastewater, it is easily recognizable and damages the aesthetic nature of the environment. Many dyes used in these industries are difficult to degrade, as they are generally stable to light and oxidizing agents, as well as resistant to aerobic digestion.…”
Section: Introductionmentioning
confidence: 99%
“…6 This dye synergizes dermatitis to sensitive skin and causes irritation to eyes. Besides, its thermal decomposition emits toxic fumes of CO, CO 2 and NO. 7 Due to these severe problems, water contamination originated from the dyeing and finishing in textile industry has become a major concern.…”
Section: Introductionmentioning
confidence: 99%